Dictionaries and Vocabulary Learning - Conceição, Mariney Pereira (The ESPecialist, 2011)
This study investigates dictionary contributions to word retention in foreign language learning. Participants were 51 students in an English for Specific Purposes class in a public university in Minas Gerais. Data were analyzed quantitatively. Although most of the students used a dictionary during the reading task, results do not indicate important contributions of the use of this strategy to word retention.